ABUNDANCE AND BIOMASS ESTIMATES OF COMMERCIAL FISH SPECIES USING HYDRO-ACOUSTIC METHOD IN JAKARTA BAY, INDONESIA - Andria Ansri Utama; Setiya Triharyuni (Research Center for Fisheries, 2015)
The Jakarta Bay is known as a fishing ground area for several traditional types of fishing gears. The fishery has important role to provide nutrition, sustainable livelihoods, and poverty alleviation around the area. Abundance estimation of commercial fish species in the Jakarta Bay is essential particularly comparable of series data in order to evaluate the potential changes in distribution and abundance. The purpose of this study is analyzing the distribution of commercial fish species in the Jakarta Bay and estimate their abundance and biomass. Fish assemblages were concentrated in the eastern and central part of bay. Apparently salinity and DO associated with rich density of phytoplankton and zooplankton may explain the spatial variability of short-bodied mackerel and pony fish, while assemblages pattern of spiny hairtail and croaker might be driven by the availability of small planktivorous fish as their diet. The most abundant commercial fish in the Jakarta Bay are Short-bodied mackerel (Rastrelliger brachysoma), Ponyfish (Leiognathus sp.), Croaker (Johnius sp.) dan Spiny hairtail (Lepturacanthus savala) respectively. Furthermore, biomass estimates for those species showed short-bodied mackerel has the highest biomass followed by spiny hairtail, croaker, and ponyfish.